Nauczanie języka sąsiada od przedszkola do zakończenia edukacji – kluczem do komunikacji w Euroregionie Pomerania. Założenia teoretyczne, cele i wstępne wyniki projektu - Bielicka, Małgorzata; Olpińska-Szkiełko, Magdalena (Neofilolog, 2022)
The paper presents a report on the implementation of the educational project Teaching the neighbours’ language from kindergarten to the end of education - the key to communication in the Euroregion Pomerania co-financed by the European Regional Development Fund (ERDF) under the Interreg VA Cooperation Program Mecklenburg-Vorpommern/Brandenburg/Poland. 24 educational institutions in Poland and 33 educational institutions in Germany took part in the project. 3,771 children and 821 teachers and kindergarten educators participated in project events. The number of lessons conducted during the project was over 30,000. In addition to school education, the project covered numerous meetings of Polish and German children and youth, workshops for teachers, educational forums for parents and others. The project developed curricula for German as a language of the neighbours at all educational stages and in all types of Polish schools, as well as numerous multimedia teaching materials, such as educational games, worksheets, educational films, etc. This paper describes the project, its theoretical and practical foundations and its results.